PKM Pemberdayaan Senam di Dusun Tlogo Kecamatan Tuntang - Setiyawan Setiyawan; Bertika Kusuma Prastiwi; Yulia Ratimiasih; Utvi Hinda Zhannisa; Fajar Ari Widiyatmoko (Universitas PGRI Semarang, 2020)
The purpose of this community service is to provide knowledge and theories about gymnastics, and equip petanque game skills. The activity was carried out three times in Tlogo Hamlet, Tuntang District, Semarang Regency with a period of 3 months. The number of participants who took part in this program was 30 people. The methods used by the Service Team in providing (delivering) training materials are: (1) Lectures, (2) Questions and Answers, (3) Demonstrations, and (4) Practices. The outputs of this activity are: 1) Public knowledge of gymnastics skills with good and correct techniques. 2) The skills of gymnastics in Tlogo Hamlet, Tuntang District, Semarang Regency will increase motivation to continue exercising. 3) The ability to use existing land in the area of Tlogo Hamlet, Tuntang District, Semarang Regency which can be used for exercising. 4)As suggestions for this activity, among others: 1) increasing attention from the local government to build gymnastic facilities and infrastructure and 2) for residents to maintain and manage the existing facilities and infrastructure.Keyword: Gymnastics, UPGRIS, Dusun Tlogo